Determination of the London penetration depth of FeSe0.3Te0.7 thin films by scanning SQUID microscope. (1st July 2015) - Lin, H T; Wu, S L; Wang, J W; Chen, T J; Wang, M J; Chen, J C; Wu, M K; Chi, C C
Abstract: We use the scanning SQUID microscope (SSM) to image the vortices in superconducting FeSe0.3 Te0.7 (FST) thin films. The observed peak flux value of FST is nearly a quarter of that of an accompanying Nb film. We developed a method for quantitatively determining the London penetration depth of the FST film from the known value of Nb. The obtained value, 0.88 μ m, is significantly larger than those obtained from single crystals of similar compositions by using other methods. The methodology developed for this study is useful for measuring London penetration depths of thin-film superconductors in general.